2020
DOI: 10.1002/art.41530
|View full text |Cite
|
Sign up to set email alerts
|

Imaging‐Based Uveitis Surveillance in Juvenile Idiopathic Arthritis: Feasibility, Acceptability, and Diagnostic Performance

Abstract: Objective Children with juvenile idiopathic arthritis (JIA) need regular examinations for uveitis to avoid visual morbidity from the most common extraarticular manifestation of disease. This study was undertaken to investigate the feasibility, acceptability, and performance of optical coherence tomography (OCT) imaging‐based diagnosis of uveitis. Methods This observational cross‐sectional study included children with and those without uveitis. The children underwent routine clinical examinations and anterior s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…16,17 Thus, the more robust cell markers have been used in this study. This study is also limited by the relatively small number of eyes at the higher grades of inflammation (+3 and +4 SUN ACC), a limitation typical of studies of anterior uveitis, 11,12,16,17 reflecting the 'real-world' distribution of disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Thus, the more robust cell markers have been used in this study. This study is also limited by the relatively small number of eyes at the higher grades of inflammation (+3 and +4 SUN ACC), a limitation typical of studies of anterior uveitis, 11,12,16,17 reflecting the 'real-world' distribution of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Children and their family were shown an image of hyper-reflective particles ('cells') on a cross sectional AS-OCT from a previous study 12 as part of the participant information procedure, asked to rate the acceptability of image acquisition on a 10cm visual analogue scale ("What did you think of the scan"), and invited to comment ("Please let us know if you have any other comments") on study aims.…”
Section: Reference and Index Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings of low adoption of LFP across the UK is consistent with other evidence of poor uptake of the technology internationally ( 44 ). Anterior segment optical coherence tomography (AS-OCT) scanning may, in future, provide validated objective metrics of disease activity ( 45 , 46 ), with AS-OCT being another potential addition in an updated dataset.…”
Section: Discussionmentioning
confidence: 99%
“…In a feasibility study, AS-OCT was found to be reliable and well-tolerated for quantitative evaluation of JIA-associated uveitis. 47 Using a cohort of children with uveitis and normal controls, Akbarali et al 47 evaluated the correlation of AS-OCT cell with slit lamp exam, and AS-OCT was found to have a sensitivity of 91.7% and specificity of 85.7% for detecting anterior chamber cell in this population.…”
Section: Imaging In Pediatric Uveitismentioning
confidence: 99%